Pengaruh Model Reward and Punishment Berbantuan Media PAHUPANCA terhadap Hasil Belajar Pendidikan Pancasila di Sekolah Dasar - Rondli, Wawan Shokib; Moh Najibul Faiz; Muhammad Baron Naftali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays a crucial role in shaping character and national values from an early age. However, low student motivation and the lack of variety in teaching methods pose challenges in improving learning outcomes at the elementary school level. This study aims to analyze the influence of the reward and punishment model assisted by PAHUPANCA media on learning outcomes in Pancasila Education at SD 2 Megawon. The research adopts a quantitative approach with a quasi-experimental design. The subjects of the study were fifth-grade students divided into two groups: an experimental group that applied the reward and punishment model using PAHUPANCA media, and a control group that used conventional teaching methods. Research instruments included learning outcome tests and student activity observation sheets. The analysis results showed a significant difference in learning outcomes between the experimental and control groups. The application of the reward and punishment model with PAHUPANCA media proved effective in increasing student engagement, motivation, and understanding of Pancasila Education material. These findings indicate that the use of innovative, media-based teaching strategies can positively impact the quality of learning. Therefore, PAHUPANCA media is a feasible alternative for implementing Pancasila Education at the elementary level to strengthen the internalization of Pancasila values more effectively.